Enacted Pedagogical Content Knowledge Profiles of Chemistry Teachers - Hatice Belge Can (Journal of Educational Issues, 2024)
This research focuses on chemistry teachers’ enacted pedagogical content knowledge (ePCK) in equilibrium in chemical reactions. The enactment dimension of this pedagogical content knowledge (PCK) encompasses enacted knowledge and skills as well as those embedded in practice concerning the Refined Consensus Model of PCK, the most recent PCK model in science education. As ePCK plays out throughout the whole pedagogical cycle, it was conceptualized as to exist in three forms, such that ePCKP, ePCKT, and ePCKR. While ePCKP and ePCKR represent the knowledge and skills that a teacher uses for planning and reflecting respectively, ePCKT is related to what a teacher does in the classroom. The holistic nature of ePCK was investigated by using multiple data sources in real-life contexts. Specifically, pre-and post-observation interviews and lesson observations were used to elicit ePCK profiles and to provide triangulation. The grand rubric was customized for use both as an interview protocol and as an observational protocol for analyzing all of the three dimensions of ePCK around the analytical parameters of knowledge and skills related to curricular saliency, conceptual teaching strategies, and student understanding of science. Results revealed that chemistry teachers’ ePCK profiles are not uniform across planning, teaching, and reflecting phases, ePCK components, and evaluation criteria. Chemistry teachers perform highest in reflection concerning conceptual teaching strategies and lowest in teaching in terms of curricular saliency. Recommendations for science PCK research were shared.